Corporate governance that 'works for everyone': promoting public policies through corporate governance mechanisms. Issue 2 (3rd July 2018) - Choudhury, Barnali; Petrin, Martin
ABSTRACT: Corporate governance mechanisms are traditionally seen as devices for reducing agency costs between shareholders and managers in the context of private ordering. More recently, however, the UK and other governments have embraced regulations in the field of corporate governance as tools through which to impose public responsibilities on corporations. Among others, corporate governance mechanisms have been relied on to equalise wealth distribution, promote equality in the labour force, and pursue environmental goals. This article assesses the justification, utility, and efficacy of using corporate governance to promote public aims. It finds that while it may be appropriate for corporate governance mechanisms to include public goals, the current overreliance on disclosure requirements and on indirect regulation to address societal issues is misguided. Instead, the article suggests that governments should view corporate governance mechanisms with public policy goals as complementary strategies, and not as substitutes, to direct external regulation.